2022
DOI: 10.1177/17562864221133163
|View full text |Cite
|
Sign up to set email alerts
|

S1P receptor modulators and the cardiovascular autonomic nervous system in multiple sclerosis: a narrative review

Abstract: Sphingosine 1-phosphate (S1P) receptor (S1PR) modulators have a complex mechanism of action, which are among the most efficient therapeutic options in multiple sclerosis (MS) and represent a promising approach for other immune-mediated diseases. The S1P signaling pathway involves the activation of five extracellular S1PR subtypes (S1PR1–S1PR5) that are ubiquitous and have a wide range of effects. Besides the immunomodulatory beneficial outcome in MS, S1P signaling regulates the cardiovascular function via S1PR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 165 publications
0
5
0
1
Order By: Relevance
“…When treating patients with S1P receptor modulators, the most important clinical consideration is the effect of initial dosing on heart rate and subsequent hypertension 72 . Clinicians should follow the recommended guidelines for initial titration of ozanimod until day 7, ponesimod until day 14, and siponimod until day 4 and day 5 to reach the 1 and 2 mg maintenance dose, respectively 7–9 .…”
Section: Clinical Considerations When Prescribing S1p Receptor Modula...mentioning
confidence: 99%
See 1 more Smart Citation
“…When treating patients with S1P receptor modulators, the most important clinical consideration is the effect of initial dosing on heart rate and subsequent hypertension 72 . Clinicians should follow the recommended guidelines for initial titration of ozanimod until day 7, ponesimod until day 14, and siponimod until day 4 and day 5 to reach the 1 and 2 mg maintenance dose, respectively 7–9 .…”
Section: Clinical Considerations When Prescribing S1p Receptor Modula...mentioning
confidence: 99%
“…When treating patients with S1P receptor modulators, the most important clinical consideration is the effect of initial dosing on heart rate and subsequent hypertension. 72 Clinicians should follow the recommended guidelines for initial titration of ozanimod until day 7, ponesimod until day 14, and siponimod until day 4 and day 5 to reach the 1 and 2 mg maintenance dose, respectively. 7 , 8 , 9 First‐dose monitoring is recommended depending on the specific agent and comorbidities in a setting where resources are available to appropriately manage symptomatic bradycardia as described in Table 4 for fingolimod, ponesimod, and siponimod.…”
Section: Clinical Considerations When Prescribing S1p Receptor Modula...mentioning
confidence: 99%
“…Ihre Wirkungen sind jedoch selektiver auf den S1P-Rezeptor vom Subtyp 1 und auf Lymphozyten, wodurch die Nebenwirkungen verringert werden. Ozanimod und Siponimod binden zudem mit hoher Affinität an die S1P-Rezeptoren 1 und 5 und haben nur eine geringe oder gar keine Wirkung auf S1P2, S1P3 und S1P4 [25].…”
Section: Was Für Wen?unclassified
“…S1P also inhibits heart rate, mainly by activating S1PR1. Several studies have reported that long-term treatment with S1PR modulators could reduce cardiac autonomic activation and decrease heart rate variability by binding S1PRs to trigger G protein-gated inwardly rectifying potassium (GIRK) channels on cardiac myocytes [68,69]. Atrial GIRK channels are activated via Gβγ to induce a transient decrease in heart rate.…”
Section: Effects Of S1p In the Heartmentioning
confidence: 99%